Stent graft in abdominal aortic aneurysm collapsed suddenly after thoracic endovascular aortic repair. Issue 12 (9th December 2021) - Takagi, Sho; Goto, Yoshihiro; Yanagisawa, Junji; Nakasu, Akio
Abstract : Stent graft collapse due to aortic dissection is an extremely rare event. Although endovascular aneurysm repair (EVAR) and thoracic endovascular aortic repair (TEVAR) are increasingly being performed, various complications can occur. We report a case of collapse of a stent graft, which was used to repair an abdominal aortic aneurysm (AAA) after TEVAR for thoracic aortic aneurysm (TAA). A 72-year-old man with a 77 mm AAA and 60 mm TAA underwent EVAR and a TEVAR 2 months later, respectively. CT performed after the TEVAR showed thoracic aorta dissection with associated AAA stent graft collapse. The graft collapsed was due to superior mesenteric artery obstruction. An emergency TEVAR was performed, and the procedure improved the collapsed graft; however, the endoleak of the AAA stent graft persisted. The AAA expanded over several days, warranting an open repair. Our case provides an insight into the cautionary indications for endovascular therapy.